Role of portocaval shunting in the era of liver transplantation - B. N. Kotiv; I. I. Dzidzava; A. A. Kochatkova; A. V. Smorodsky (Трансплантология (Москва), 2018)
Shortage of donor organs is a major factor that limits the use of orthotopic liver transplantation in cirrhosis. In this connection, the use of various methods for surgical correction of portal hypertension continues to be urgent.Subjects and methods. One hundred and seven patients with portal hypertension caused by hepatic cirrhosis were surgically treated. Before surgical treatment, gastroesophageal hemorrhages were noted in 64 (59.8%); 27 (35.5%) patients had more than 2 episodes of gastroesophageal hemorrhages. The mean MELD score was 8.54±3.31. Distal splenorenal anastomosis (DSRA) was performed in 46 patients; different modes of partial bypass surgery were made in 61 patients. The rate of plasma indocyanine green elimination was estimated. Liver biopsy specimens were histomorphometrically examined.Results. First-to-second degree encephalopathy developed in 15.2 and 15.1% of cases after DSRA and partial anastomoses, respectively. Postoperative mortality was 9.3%. Early postoperative relapses of gastroesophageal hemorrhages were observed in 12 patients. Survival was comparable in patients who had undergone portocaval or partial anastomoses. The median lifetime was 60±5.1 months. Conclusion. Following portocaval anastomosis, the lifespan in patients after portocaval shunting is determined by the degree of hepatic decompensation. Major risk factors, such as the degree of the edematous-ascitic syndrome, the level of serum albumin, total bilirubin, international normalized ratio, and residual indocyanine concentrations at minute 15, were identified. The sensitivity and specificity of this group of criteria are 84.2 and 70.0%, respectively.